The Practical Philosophy of Al-Farabi - and Avicenna: A Comparison - (:unkn) unknown (SCIENTIFIC STUDIES ASSOC-ILMI ETUDLER DERNEGI-ILEM, 2019)
This article compares the approaches to practical philosophy of the two most significant Muslim philosophers of the classical period, al-Farabi (d. 950) and Ibn Sina (d. 1037). Initially, I will examine their classification of the practical sciences and show their formal differences, and then question whether these differences point to a fundamental disagreement about the source of practical knowledge. One of my conclusions is that al-Farabi clearly separated the intellectual and independent concept of practical philosophy from the religious sciences, whereas Ibn Sina's standpoint is religious-based, dependent, and partially covered by Islamic jurisprudence. As the latter emphasizes these various points in separate passages about the source of practical knowledge, a holistic and illustrative combination of these passages is required. Thus, by citing and discussing all of these passages, I suggest that Ibn Sina not only accepted the prophetic legislation of the practical sciences, but also provided an epistemological background that makes it possible to take account of the earlier Greek and Muslim moral philosophers' legacy. Finally, I also point out that the main reason for these philosophers' differences over practical philosophy is their disagreement about the relation between religion and philosophy.
Keywords: Al-Farabi; Ibn Sina/Avicenna; ethics; morality; moral philosophy; al-hikmat al-'amaliyya; classification of practical sciences